2012
DOI: 10.1103/physrevd.85.104028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a weak electromagnetic field on particle acceleration by a rotating black hole

Abstract: We study high energy charged particle collisions near the horizon in an electromagnetic field around a rotating black hole and reveal the condition of the fine-tuning to obtain arbitrarily large center-of-mass (CM) energy. We demonstrate that the CM energy can be arbitrarily large as the uniformly magnetized rotating black hole arbitrarily approaches maximal rotation under the situation that a charged particle plunges from the innermost stable circular orbit (ISCO) and collides with another particle near the h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 18 publications
4
59
0
Order By: Relevance
“…where ρ 0 denotes the particle initial position (its radial coordinate), and u φ is charged particle angular velocity (39) given by the relation…”
Section: Charged Particle Dynamics In Asymptotically Flat Region Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…where ρ 0 denotes the particle initial position (its radial coordinate), and u φ is charged particle angular velocity (39) given by the relation…”
Section: Charged Particle Dynamics In Asymptotically Flat Region Of Tmentioning
confidence: 99%
“…The study of the charged particles 'kicked' from the innermost stable circular orbit (ISCO) in the equatorial plane and hence escaping to infinity along the axis of symmetry has been treated in [33] -because the charged particle motion in the vicinity of a black hole immersed into magnetic field is chaotic, the resulting final ejection velocity does not depend continuously on the initial conditions [28]. It has been demonstrated that collisions of particles in the vicinity of black holes could be enhanced by the external magnetic fields [39][40][41][42][43], but these processes can be observationally efficient especially in the field of Kerr naked singularities [44]. The relation of the quasi-circular equatorial motion of charged test particles around black holes immersed in the magnetic field to the high-frequency quasiperiod oscillations observed in some microquasars has been demonstrated in [29].…”
Section: Introductionmentioning
confidence: 99%
“…There-fore, the CM energy of collision expected to depend both on spin and charge. The BSW scenario is generalized to charged BHs [5], the Kerr-Newman family of BHs [6] and general rotating BHs [7]. It is shown that, for a nearextremal charged BH, there always exists a finite upper bound for CM energy, which decreases with the increase of the charge Q.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is a simplified problem, the dynamics are still nonintegrable due to the lack of a third constant of motion (the Carter constant) in the presence of a magnetic field. If we focus on equatorial motion, a semi-analytical approach is possible [10][11][12], but a general orbit requires numerics [13][14][15][16][17]. More specifically, we consider the motion of a charged particle kicked out from the equatorial plane, and investigate the conditions under which such a particle can escape to infinity.…”
Section: Introductionmentioning
confidence: 99%